2003
DOI: 10.4102/sajbm.v34i2.680
|View full text |Cite
|
Sign up to set email alerts
|

Employee perceptions of share ownership schemes: An empirical study

Abstract: The objective of this study was to investigate some of the problems associated with the introduction and successful management of Employee Share Ownership Schemes (ESOPs). An ESOP is a participative management approach that appeals to some of the needs of both employees and management. The study considered how perceptions of ESOPs can be influenced and managed through managerial antecedents such as trust, empowerment and communication, and empirically measures their impact on outcome variables such as organisa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…), increased retention (Dansereau, Cashman and Graen ; Graen, Novak and Sommerkamp ), improved organizational citizenship behavior (Kim, O'Neil and Cho ), subordinates' increased communicative responsiveness (Borchgrevink and Boster ), and improved performance ratings (Farh et al. ), as well as increased positive attitudes among subordinates, such as organizational commitment (Ansari, Hung and Aafaqi ; Lee ; Mazibuko and Boshoff ; Nystrom ), a higher level of trust (Testa ), psychological empowerment (Kim and George ), job satisfaction (Dulebohn et al. ; Erdogan and Enders ; Liao, Hu and Chung ) and perception of empowerment (Deci, Connell and Ryan ).…”
Section: Conceptual Background and Hypothesesmentioning
confidence: 99%
“…), increased retention (Dansereau, Cashman and Graen ; Graen, Novak and Sommerkamp ), improved organizational citizenship behavior (Kim, O'Neil and Cho ), subordinates' increased communicative responsiveness (Borchgrevink and Boster ), and improved performance ratings (Farh et al. ), as well as increased positive attitudes among subordinates, such as organizational commitment (Ansari, Hung and Aafaqi ; Lee ; Mazibuko and Boshoff ; Nystrom ), a higher level of trust (Testa ), psychological empowerment (Kim and George ), job satisfaction (Dulebohn et al. ; Erdogan and Enders ; Liao, Hu and Chung ) and perception of empowerment (Deci, Connell and Ryan ).…”
Section: Conceptual Background and Hypothesesmentioning
confidence: 99%
“…In doing so, it proposes that leaders develop qualitatively different types of relationships with their employees. Since the introduction of the LMX theory, a number of research studies have revealed that a high quality of LMX predicts a lower employee turnover (Cole, 1995), more positive performance evaluations (Cole, 1995), and greater organizational commitment (Mazibuko & Boshoff, 2003).…”
mentioning
confidence: 99%
“…In addition, there has been a sustained growth of a black middle class since 1994 (Burger & Van den Berg, 2004) and stateowned enterprises have vigorously promoted both preferential procurement programmes, as well as transformation of their ownership and management structures (Southall, 2004;. Conversely, many critics suggest that BEE is a sham, that it has only benefited the politically connected elite and that it is a front for maintaining the historic demographics of ownership (Engdahl & Hauki, 2001;Mazibuko & Boshoff, 2003;Southall, 2004;Freund, 2006). Finally, there are claims that BEE deters foreign investment (Thompson, 2004;Southall, 2004;Butler, 2006) and that the transfer of ownership to BEE partners could tie up R450 billion (Cargill, 2005:21) This study investigates the share performance of companies listed on the JSE and involved in BEE transactions, specifically in terms of its ability to create shareholder wealth.…”
Section: Introductionmentioning
confidence: 99%